Simulation Research on Hollow Cavities in the Body of Dikes and Dams by Geophysical Methods - Minh, Vu Duc; Chung, Do Anh (VNU Journal of Science: Mathematics - Physics, 2013)
Abstract: This paper presents the results of simulation study of hollow caves in the body of dikes, dams through theoretical modeling and calculation based on the knowledge of Mathematics, Informatics, Physics in general and Geophysics in particular and also the information processed by the software of EarthImage 2D and Reflex 2D on the methods of multi-electrode electrical sounding and ground penetrating radar. From there, it is possible to draw conclusions on the applicability of both methods for finding, identifying hollow cave, and also looking at ways to conduct field work appropriate to improve the efficiency of the methods mentioned above. These results will be applied as the basis for the discovery of the hollow cave of dikes and dams inVietnam. Keywords: Simulation, hazard, hollow cave, dike, dam.